Promoting Equalization and Local Control in Financing Colorado's Schools - Judith K. Mathers; Richard A. King (Educational Considerations, 1997)
Finding solutions to the perennial problems of inadequate operating revenues…proves as difficult as scaling any of Colorado's famous '14'ers.